(In)consistent? The mathematics teaching of a novice primary school teacher - Palmér, Hanna (NOMAD Nordic Studies in Mathematics Education, 2012)
This article focuses on the mathematics teaching of Helena, a Swedish novice teacher. Helena is one of seven teachers in a case study of primary school mathematics teachers’ professional identity development. She is also an example of a teacher whose mathematics teaching, from an observer’s perspective, may appear inconsistent with her talk about mathematics teaching. However, in this article a conceptual framework aimed at analysing professional identity development will be used making the process of her mathematics teaching visible and then her mathematics teaching appear as consistent.